Dampak Persepsi Risiko, dan Financial Technology pada Minat Masyarakat untuk Berinvestasi - Pipin Fitriasari; Maria Yanida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the impact of risk perception, financial technology, on the interest of the people of Balikpapan City to invest in the capital market. This type of research is quantitative research, with a questionnaire as the research instrument. The population in this research is the people of Balikpapan City with several criteria. The sampling technique uses incidental sampling. Based on the sampling method, a sample of 216 respondents. The results of this research show that risk perception, financial technology have a positive and significant effect on the interest in investing in the capital market among the people of Balikpapan City.